CSF concentration of cefotaxime in adult patients with pneumococcal meningitis: a multicentre retrospective study. (13th June 2021) - Le Turnier, Paul; El Helali, Najoua; Guilhaumou, Romain; Pilmis, Benoit; Revest, Matthieu; Velly, Lionel J.; Leroy, Anne-Gaëlle; Duval, Xavier; Lemaitre, Florian; Gregoire, Matthieu
Abstract: Background and objectives: Pneumococcal meningitis is a devastating disease that requires adequate meningeal antibiotic penetration to limit the mortality. Despite a large usage in this indication, data about CSF concentration of cefotaxime during pneumococcal meningitis in adults are scarce. Therefore, we aimed to describe the CSF concentration obtained after high-dose cefotaxime administration in adult patients treated for Streptococcus pneumoniae meningitis. Patients and methods: In this multicentre, observational, retrospective study, cases of adult patients with S. pneumoniae meningitis hospitalized between January 2013 and October 2019 for whom cefotaxime concentration was measured in CSF were reviewed. Results: Cefotaxime concentration was analysed in 44 CSF samples collected among 31 patients. Median (IQR) age was 61 years (52–69). Dexamethasone was administered in 27 subjects. Median (IQR) cefotaxime daily dosage was 15 g (12–19), corresponding to 200 mg/kg (150–280). CSF samples were collected approximately 5 days after cefotaxime initiation. Median (IQR, range) cefotaxime CSF concentration was 10.3 mg/L (4.8–19.3, 1.2–43.4). Median (range) MIC for Streptococcus pneumoniae was 0.25 mg/L (0.008–1) ( n = 22). The median (IQR, range) CSF/MIC ratio was 38 (12–146, 4–1844). Twenty-five CSF concentrations (81%) were above 10 times the MIC. Cefotaxime was discontinued in two patients for toxicity. In-hospital mortality rate was 29%. Conclusions: Adult patients with pneumococcal meningitis treated with a high dose of cefotaxime (200 mg/kg/day) had elevated CSF concentrations with satisfying pharmacokinetics/pharmacodynamics parameters and tolerability profile. This study brings reassuring pharmacological data regarding the use of high-dose cefotaxime monotherapy for treating pneumococcal meningitis with susceptible strains to cefotaxime.